(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The discovery of a helmet in the waters of the river Avión, we reflect on the nature of such offering practices. We considered the relation with the site characteristics. The results allow us to consider this case as paradigmatic of the general dynamic of offering weapons to water. The tradition can be characterized as protohistoric and increases it’s meaning by the site selected for this offering with sacred clear implications. This paper compares this discovery with other similar places.